THE INFLUENCE OF CUSTOMIZED LEARNING MATERIALS ON ENGLISH LANGUAGE COMPETENCY IN INTERMEDIATE LEARNERS (CAHIERS MAGELLANES-NS, 2024)
The present paper discusses the impact of tailored material on the intermediate-level proficiency of students in the English language. Tailor-made material, designed with the primary aim of focusing on specific aspects of language that may be of interest or of most interest to them, aims at maximizing both relevance and retention. The current study focuses on middle learners with the aim to connect the base and higher levels of English proficiency levels that challenge learners with some unique characteristics of idiomatic language, complex grammar, and situational vocabulary. The research adopted a mixed-methods approach, with both pre- and post-assessments being considered as measures of competency along with qualitative feedback about the experience of the learners. Results suggest fluency, comprehension, and confidence in using the language. Participants particularly reported a higher motivation and confidence level, which they directly related to the relevance and clarity of the material. The findings would thus identify significance in the adaptation of resources to learners' needs at developing stages, especially intermediate. This research serves as invaluable contribution to educators looking for the best means to encourage long-term language development. Generally speaking, the results of this study suggest that customized materials are a necessary resource for meaningful and interesting learning of English.